Hierarchical porosity inherited by natural sources affects the mechanical and biological behaviour of bone scaffolds. Issue 4 (April 2020) - Sprio, Simone; Panseri, Silvia; Montesi, Monica; Dapporto, Massimiliano; Ruffini, Andrea; Dozio, Samuele M.; Cavuoto, Riccardo; Misseroni, Diego; Paggi, Marco; Bigoni, Davide; Tampieri, Anna
Abstract: A 3-D porous apatite scaffold (B-HA), recently obtained through biomorphic transformation of a natural wood, is investigated on its multi-scale porous structure determining superior biological and mechanical behaviour. B-HA shows a hierarchically organized architecture with wide aligned channels interconnected with smaller tubules, thus recapitulating in detail the lymphatic network of the original wood template. As induced by its biomimetic architecture, B-HA displays values of tensile/compressive strengths and stiffness, higher than values usually measured in sintered ceramics with isotropic porosity. Furthermore, B-HA shows uncommon toughness for a pure ceramic body, plus a tensile/compressive-strength ratio higher than one, so that the material occupies a zone in the Ashby map where ceramics are normally absent. From biological viewpoint, cell co-culture tests in bioreactor are shown to report encouraging results in enhancing the complex tissue regeneration process, thus making B-HA promising as a scaffold able to promote bone regeneration, particularly for large bone defects.